Can the Biophilia Hypothesis Be Applied to Long-Duration Human Space Flight? A Mini-Review - Neilson, Brittany N.; Craig, Curtis M.; Altman, George C.; Travis, Alexandra T.; Vance, Joseph A.; Klein, Martina I. (Frontiers in Psychology, 2021)
The International Space Station (ISS) has around 3–5 crew members on-board at all times, and they normally stay on the ISS for about 5–7months in duration. Since March 2020, 170 long-duration space missions have occurred on the ISS. Thus, long-duration space missions are an integral part of space exploration and will only continue to expand in duration as missions to the Moon and Mars are on the horizon. However, long-duration space missions present several challenges to human crew members. Most of these challenges have been associated with physiological adaptation to microgravity, including motion sickness, muscle atrophy, and cardiovascular deconditioning. While not as well-studied, another major factor to consider when planning long-duration space missions is the psychological impact of the environment on the astronauts. Astronauts living in space will be unable to access natural landscapes and other environments found to have restorative effects on psychological stress and overall well-being. On top of being unable to access these restorative natural environments, astronauts will also be exposed to the stressful, unfamiliar environment of space. The purpose of this mini-review is to first summarize the literature related to stressors associated with space. Next, an overview of the large breadth of literature on the biophilia hypothesis and restorative environments will be provided, as these may serve as relatively simple and cost-effective solutions to mitigate the stress faced during long-duration space missions. Lastly, considerations related to the design of such environments in a space capsule as well as future directions will be presented.